Transarterial chemoembolization using drug-eluting bead compared with radiofrequency ablation for treatment of single small hepatocellular carcinoma: a pilot non-randomized trial - Tae Hoon Kim; Na Hye Kim; Jin Dong Kim; Young Nam Kim; Yu Jin Kim; Eun Jung Kim; Ki Deok Yoo; Choong Heon Ryu; Ha Hun Song; Hyun Kim (Journal of Liver Cancer, 2021)
Background/Aims Surgical resection, transplantation, and radiofrequency ablation (RFA) are generally accepted as amenable treatments for small hepatocellular carcinoma (HCC). Recently drug-eluting beads (DEB) which had several treatment advantages were introduced for transarterial chemoembolization (TACE). The aim of this study was to evaluate feasibility and safety of DEB-TACE compared with RFA for the treatment of single small HCC. Methods In this pilot non-randomized trial, we assessed retrospective data of 40 patients who underwent DEB-TACE (n=21) or RFA (n=19) for single small (≤3 centimeter in greatest dimension) HCC. The primary outcomes were tumor response and time to recurrence. The secondary outcome was treatment-related complications. Results Complete response rate to DEB-TACE and RFA after first follow-up assessment was 90.5% and 94.7%, respectively (P=1.000). During mean follow-up of 87.6 months (95% confidence interval, 74.4–102), 7 patients experienced local recurrence. The 6- and 12-month cumulative local recurrence rate was 5.0% and 21.8% in DEB-TACE vs. 11.1% and 17.0% in RFA group (P=0.877). A total 14 distant intrahepatic recurrences were developed and 12- and 24-month cumulative distant intrahepatic recurrence rate was 20.6% and 42.7% in DEB-TACE vs. 17.2% and 36.3% in RFA group (P=0.844). Two patients experienced gangrenous cholecystitis after DEB-TACE requiring cholecystectomy as treatment-related adverse event. Conclusions Tumor response and recurrence rate after single session of DEB-TACE or RFA were similar. DEB-TACE could be applied selectively in patients with a single small HCC if the other therapeutic modality is unfeasible.